PP.29.08: HYPERTENSION PREVALENCE AND MANAGEMENT IN PORTUGAL. (June 2015) - Macedo, M.; Ferreira, R.
Abstract : Objective: Hypertension is the leading risk factor contributing for the cardiovascular morbidity and mortality in the Portuguese population. It's management is predominantly undertaken by primary physicians. Estimates of the prevalence, treatment and control of Blood Pressure (BP) in the primary care populations are needed to adequately address the high burden of hypertension in Portugal. Design and method: A retrospective analysis of patient-based electronic medical records was conducted during the year of 2013. To examine the effect of regular General practitioner (GP) management and control on BP across at least two annual visits. A subgroup of patients with elevated BP and age equal or more tan 18 years old, were selected in a total of 2.639 millions patients (58, 1 % women). Hypertension was defined as Systolic BP and or Diastolic BP equal or mores than 140/90 mmHg. Results: The mean value for SBP was 130, 8 ± 12, 4 mmHg (men 133, 9 ± 11, 9, and women 129, 0 ± 11, 7) and DBP 75, 3 ± 12, 8 mmHg (men 76, 3 ± 12, 7 women 74, 7 ± 12, 8). The overall prevalence of hypertension was 29, 1% (men 26, 0% and women 31, 8%). Among those patients under hypertensive treatment, the control rates were 33, 9% (men 31, 4% and women 35, 8%). The main classes of antihypertensive prescribed were tiazide diuretics 27, 2% (men 23, 7% and women 29, 7%), Beta-blockers 27, 0% (men 26, 5% and women 27, 4%), calcium channel blockers 20, 2% (men 21, 1% and women 19, 5%) and blockers of Renin Angiotensin Aldosterone System (RAAS) 80, 8% (men 84, 8% and women 77, 9%). Conclusions: The prevalence of hypertension was lower than the results of PAP and PHYSA studies. Arterial blood pressure control was optimum in only three out of ten in the subgroup of Portuguese patients aged 18 years or older. Blood pressure control assessment was significantly better in women. A more intensive approach in the management of the BP in primary care is required to ensure that more patients achieve BP control targets.